Modern World History - Allosso, Dan; Williford, Tom (Open textbook library., 2021)
Welcome to Modern World History! This is the textbook for an undergraduate survey course taught at all the universities and most of the colleges in the Minnesota State system. Similar courses are taught at institutions around the United States and the world, so the authors have made the text available as an open educational resource that teachers and learners can read, adapt, and reuse to meet their needs. We’d like to hear from people who have found the text useful, and we’re always open to questions and suggestions.